Electrochemical Deposition of Hydroxyapatite Co-Substituted By Sr/Mg Coating on Ti-6Al-4V ELI Dental Alloy Post-MAO as Anti-Corrosion - AlMashhadani, Haider Abdulkareem; Saleh, Khulood Abed (Iraqi Journal of Science, 2020)
This work involved the co-substitution of the two bioactive ions of strontium and magnesium into the hydroxyapatite (HA) coating which was then electrochemically deposited on Ti-6Al-4V ELI dental alloy (Gr.23) before and after treatment by Micro Arc Oxidation (MAO). The deposited layers were characterized by scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD), and Fourier transform infrared spectroscopy (FTIR). The adhesion strength of the coating layer was estimated by using pull-off adhesion test. The adhesion strength of Sr/Mg-HA on the Ti-6Al-4V ELI dental alloy after MAO treatment was 1.79 MPa, which was higher than that before MAO treatment (1.62 MPa). The corrosion behavior of the alloy in artificial saliva environment at temperature ranged 293-323K was assessed by means of electrochemical techniques and potentiodynamic polarization curves. The corrosion protection to the alloy at 293K was increased from 67.98% before treatment by MAO to 75.87% after treatment. The antimicrobial properties of the coated alloy were evaluated against different bacteria and oral fungi (Candida).